Brakes to the diffusion of a two‐sided social innovation: A case study on microinvestors' perspectives. (4th May 2020) - Ashta, Arvind; Estapé‐Dubreuil, Glòria; Hédou, Jean‐Pierre; Bourcieu, Stéphan
Abstract: The diffusion of social innovation requires overcoming institutional resilience and ignorance of innovation. The forces of the marketing and development work of the organization managers may be unable to overcome the strength of the institutional framework. These institution brakes include soft norms such as values, ideology, and psychology, as well as hard norms such as regulations. Spurts in the diffusion of the innovation require exogenous crises to overcome the friction.